EVALUATION OF DPPH RADICAL SCAVENGING ACTIVITY AND REDUCING POWER OF FOUR SELECTED MEDICINAL PLANTS AND THEIR COMBINATIONS (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
Reactive oxygen species [ROS] cause oxidative damage to the tissues and protection from such damages are provided by endogenous and exogenous antioxidants. Plant based antioxidants are preferred due to the multiple mechanisms of actions and of the phytochemicals present in them. 80% alcoholic extract of leaves of Aloe vera, Bacopa monniera, Moringa oleifera and rhizome of Zingiber officinale was tested individually and in combination in equal proportion of each extract for DPPH scavenging activity and reducing power. The results indicate that the combination of the extract has better DPPH scavenging action and reducing power compared to the individual plant extract indicating synergistic and supra additive effect of phytochemicals present in the extract.